BALANCED SCORECARD OF SAFETY-ORIENTED MANAGEMENT FOR THE CONSTRUCTION INDUSTRY ENTERPRISES - Tetiana Momot; Olena Filonych; Antonina Kosiak; Olena Lobach (Сучасний стан наукових досліджень та технологій в промисловості, 2021)
The article is devoted to the study of the theoretical and methodological foundations for the development of a balanced scorecard for ensuring safe-oriented management of enterprises in the construction industry. The subject of the research is a set of theoretical, methodological and practical aspects to ensure the formation of the balanced scorecard development to ensure safe-oriented management of enterprises in the construction industry. The purpose of the article is to develop theoretical and methodological provisions and substantiate practical recommendations for the formation of a model of a balanced scorecard for ensuring safe-oriented management of enterprises in the construction industry, taking into account the interests of all groups of stakeholders. Objectives of the work: to analyze modern trends in the development of enterprises in the construction industry in Ukraine; to generalize approaches to the definition of the concept of safety-oriented management; explore and organize the elements of safety-oriented management; to develop a model of a balanced scorecard for ensuring safe-oriented management in the corporate security system of enterprises in the construction industry. In the course of the study, the following methods were used: abstract-logical analysis, theoretical generalization and systematization, system analysis. The paper analyzes the dynamics of the development of enterprises in the construction industry in Ukraine in the context of the introduction of quarantine measures related to COVID-19. Factors constraining construction activities have been identified, which include financial constraints, insufficient demand, labor shortage, and weather conditions. Approaches to the definition of security-oriented management have been generalized and the definition of security-oriented management in the corporate security system has been improved. The elements of safety-oriented management are systematized with the specification of such components as risk assessment, development and implementation of security policy, definition of requirements, establishment of control and monitoring of the external and internal environment. A model of a balanced scorecard for ensuring safe-oriented management of enterprises in the construction industry has been developed. Conclusions. In the course of the study, the expediency of forming a balanced system of indicators for ensuring safe-oriented management of enterprises in the construction industry was substantiated, taking into account the dynamics of the performance of construction work during 2019-2021. The elements of the system of safe-oriented management are presented in detail and the expediency of the formation of a balanced system of indicators for ensuring the safe-oriented management of enterprises in the construction industry is substantiated. The sequence of the formation of a balanced scorecard for ensuring safety-oriented management is detailed with the specification of a scorecard for assessing strategic goals for the components of a balanced scorecard: finance, customers, internal business processes, training and development.